2023
DOI: 10.1186/s12872-023-03300-0
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed hypertension and associated factors among adults in ethiopia: a systematic review and meta-analysis

Abstract: Background Hypertension is a major public health problem, resulting in 10 million deaths annually. Undiagnosed hypertension affects more people than ever before. It is more likely to be linked to severe hypertension, which can lead to stroke, cardiovascular disease, and ischemic heart disease. Thus, this systematic review and meta-analysis aimed to synthesize the prevalence of undiagnosed hypertension and its associated factors in Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Similar to our ndings, the Ethiopian systematic review and meta-analysis study showed that, the pooled prevalence of undiagnosed hypertension was to be high in Ethiopia. Being older, having a BMI greater than 25 kg/m 2 , having a family history of hypertension, and having DM comorbidity were found to be risk factors for undiagnosed hypertension (5). This suggests some shared risk factors and the importance of awareness in managing hypertension across these African populations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar to our ndings, the Ethiopian systematic review and meta-analysis study showed that, the pooled prevalence of undiagnosed hypertension was to be high in Ethiopia. Being older, having a BMI greater than 25 kg/m 2 , having a family history of hypertension, and having DM comorbidity were found to be risk factors for undiagnosed hypertension (5). This suggests some shared risk factors and the importance of awareness in managing hypertension across these African populations.…”
Section: Discussionmentioning
confidence: 97%
“…Sub-Saharan Africa (SSA) is home to many low-and middle-income countries that have experience a shift in the burden of disease, from predominantly communicable diseases to NCDs, like hypertension. With an estimated prevalence of 5-50% (depending on the country), SSA has been experiencing an exponential rise in hypertension over the last few decades (5). A systematic review and meta-analysis revealed high prevalence of hypertension among older adults in Africa, even among rural populations, which made up 57% of overall prevalence (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Being older, overweight, and having a family history of hypertension is significantly associated with undiagnosed hypertension. 24 A study conducted in Mizan‐Aman Town, Bench Sheko Zone, Southwest Ethiopia revealed that older age, being male, low physical activity, low consumption of fruits and vegetables, and higher body mass index (BMI) were significantly associated with undiagnosed hypertension. 25 Those are drinking alcohol, diabetes mellitus, low socioeconomic status, poor knowledge, smoking, stress, physical inactivity, BMI > 25, older age, family history of hypertension, and chewing chat were significantly associated factors with undiagnosed hypertension.…”
Section: Introductionmentioning
confidence: 99%